Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - Mid-Chapter Quiz - Page 498: 22



Work Step by Step

In order to simplify the product $(2m-7)^{2}$ we must apply the rule that states that $(a-b)^{2}$=$a^{2}$-2ab+$b^{2}$, and we'll set a=2m and b=7. Therefore, $(2m-7)^{2}$=$(2m)^{2}$-2(2m)(7)+$7^{2}$ =$4m^{2}$-28m+49
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.